Targeting ER stress in skeletal muscle through physical activity: a strategy for combating neurodegeneration-associated muscle decline - Su, Zhanguo; Xiang, Lijuan (Frontiers in Molecular Neuroscience, 2025)
The pathophysiology of neurodegenerative diseases is largely driven by ER stress, contributing to cellular dysfunction and inflammation. Chronic ER stress in skeletal muscle is associated with a deterioration in muscle function, particularly in diseases such as ALS, PD, and AD, which are often accompanied by muscle wasting and weakness. ER stress triggers the UPR, a cellular process designed to restore protein homeostasis, but prolonged or unresolved stress can lead to muscle degeneration. Recent studies indicate that exercise may modulate ER stress, thereby improving muscle health through the enhancement of the adaptive UPR, reducing protein misfolding, and promoting cellular repair mechanisms. This review examines the influence of exercise on the modulation of ER stress in muscle cells, with a particular focus on how physical activity influences key pathways contributed to mitochondrial function, protein folding, and quality control. We discuss how exercise-induced adaptations, including the activation of stress-resilience pathways, antioxidant responses, and autophagy, can help mitigate the negative effects of ER stress in muscle cells. Moreover, we examine the potential therapeutic implications of exercise in neurodegenerative diseases, where it may improve muscle function, reduce muscle wasting, and alleviate symptoms associated with ER stress. By integrating findings from neurobiology, muscle physiology, and cellular stress responses, this article highlights the therapeutic potential of exercise as a strategy to modulate ER stress and improve muscle function in neurodegenerative diseases.